PENERAPAN PIDANA TERHADAP TINDAK PIDANA PENGANIAYAAN - Syafri Gunawan Nasution (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research uses qualitative research, namely by using normative and empirical juridical methods. This study aims to find out and understand and analyze the Application of Criminal Sanctions to Criminal Acts 351 of the Criminal Code concerning Persecution According to Article 351 of the Criminal Code and Considerations in imposing judgment Number: 92/Pid.B/2021/PN Kbu. Application of criminal sanctions against criminal acts 351 of the Criminal Code concerning persecution according to article 351 of the Criminal Code committed by Defendant I Roma Chandra Bin Achrulia and Defendant II Rossi Sandi Alias Ici Bin Achrulia, thus every Defendant who commits a criminal act of persecution that causes the injury of the defendant must be held accountable for his actions which basically lead to the conviction of the perpetrator, if he has committed a criminal act that meets the predetermined elements Law. as contained in the Decision of the Bumi City District Court Number: 92/Pid.B/2021/PN Kbu carried out by the defendant I Roma Chandra Bin Achrulia and Defendant II Rossi Sandi Alias Ici Bin Achrulia have deliberately committed criminal acts of mistreatment of witness Alias Didi Chandra.